Bottom-Up Approach Ship Emission Inventory in Port of Incheon Based on VTS Data - Hyangsook Lee; Hoang T. Pham; Maowei Chen; Sangho Choo (Journal of Advanced Transportation)
As a result of the rapid growth of international trade, atmospheric pollution from transportation has been more topical than ever, especially in dense hub port-cities. The shipping industry should pay more attention corresponding to its contribution to local atmospheric pollution. This paper supports the application of data collected from the vessel tracking service system with a bottom-up approach to generate a comprehensive 2019 local ship emission inventory at Port of Incheon. The calculated emission inventory presented the dominance of CO2 emission and the considerable contribution of NOx and SOx emissions, the significant contribution of auxiliary engines during the hotelling at berth during the year of 2019. Then, based on calculated emission inventory, this study suggested and simulated applicable green policies in the practice: (1) local emission control area realization, (2) vessel speed reduction program, (3) application of cold ironing, and (4) establishment of a national integrated emission platform. The combination of the three first policies could help reduce the significant volume of emitted CO (29%), NOx (30%), SOx (93%), PM10 and PM2.5 (64%), VOC (28%), NH3 (30%), and CO2 (30%).